PENGEMBANGAN KAWASAN AIR TERJUN BATU MAHASUR SEBAGAI EKOWISATA UNGGULAN DI KABUPATEN GUNUNG MAS (Developing Waterfall of Batu Mahasur as Ecotourism at the Gunung Mas Regency) : I Nyoman Surasana1, Rosdiana1, Yetri 2 - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACT Batu Mahasur waterfall area is a tourist attraction in Gunung Mas Regency, which had been utilized by the community as a place for bathing and recreation relish the waterfall environment. The management of the area has not managed well so have not been able to bring a large number of tourists, especially tourists from outside the region. The research was conducted to find out the response of the community regarding the development of Batu Mahasur waterfall area became the flagship of ecotourism object in Gunung Mas Regency. Data were collected through direct interviews with the publics (respondents) that guided by questionnaire and field survey to the waterfall area. Data analysis using Guttman scale. The results showed that community support in the development of Batu Mahasur Waterfall area became the flagship of ecotourism object in Gunung MasRegency with reaching value namely 84%. Keywords: Batu Mahasur waterfall, ecotourism, Guttman scale.